Criminal Legal Accountability on Medical Privacy Violations - Ridwan Ridwan; Isharyanto Isharyanto; Hari Purwadi (Journal of Health Policy and Management, 2019)
Background: The secret of medicine or medical secrets is the right of the patient, this secret is a moral obligation based on the norms of decency originating from Hippocratic oaths, maintaining the secret of medicine is the duty of doctors to carry out their duties and practices. This provision is regulated in Article 48 of Law Number 29 of 2004 concerning Medical Practice, if this secret is leaked it can be held liable for violators. The purpose of this study was to solve legal issues and at the same time provide a prescription regarding the need for legal sources in the form of primary legal materials and secondary legal materials.Subjects and Method: This was a systematic review with normative juridical methods to solve legal issues.Results: Legal liability for medical secrets in health service facilities can be applied to the Criminal Code (KUHP). Disputes that occur regarding doctors or health personnel are resolved through professional organizations. Doctors through the Indonesian Doctors Discipline Honorary Council (MKDKI) but MKDKI did not have the authority to examine Criminal cases. Violations of medical secrets or job secrets, legal liability is not regulated or not based on legislation in force in the health sector, but the legal liability of violations of medical secrets comes from the general Criminal Code (KUHP).Conclusion: The secret of medicine is the autonomy right of patients. Maintaining the secret of medicine is the duty of doctors to health service facilities, the secret of medicine is not absolute and can be opened in certain circumstances, but this secret can be opened in accordance with the provisions of legislation. If the secret is leaked, violators can be asked for legal responsibility, especially Article 322 of the Criminal Code.Keywords: Medical Secrets, Criminal Legal Accountability, Health Services.Correspondence: Ridwan. Masters Program in Law, Universitas Sebelas Maret, Jl. Ir. Sutami No. 36 A, Surakarta, Central Java 57126. Email: ridwanozil16@yahoo.com. Mobile: +6281237553434Journal of Health Policy and Management (2019), 4(1): 67-75https://doi.org/10.26911/thejhpm.2019.04.01.08